Kebijakan Sertifikasi Halal: Intervensi Agama-Negara dan Respon Pedagang Malioboro - laode, Abdullah (Studia Economica : Jurnal Ekonomi Islam, 2023)
The purpose of this article is to criticize halal policies in Indonesia. Halal in Indonesia was initially voluntary, and was issued by the social organization, the Indonesian Ulema Council (MUI). Then in 2014 the government under the Halal Product Guarantee Implementation Agency (BPJPH) took over through the Halal Product Guarantee Law No. 33 of 2014. Taking over halal authority from Community Institutions (MUI) caused halal which was previously voluntary to become an obligation. (mandatory). And its full implementation will take place in October 2024. The halal obligation of course means that the community, especially small and medium business actors such as those in Malioboro, are obliged to carry out halal certification. This research is field research and is qualitative in nature. From the research results, 10 informants who were interviewed by researchers, 5 informants agreed to the halal certification policy even though it was expensive, 3 informants did not agree to the halal certification policy because they had just found out that halal certification was paid, 2 other informants looked at the situation and conditions and followed it if it had been implemented sanctions from the government regarding MSMEs that do not have a halal certificate